EFFECT OF PHYSICAL ACTIVITY ON REDUCING CARDIOVASCULAR DISEASE RISK IN ADULTS: A NARRATIVE REVIEW - Patrycja Stępińska; Anastasiia Holoborodko; Ewa Wieczorkiewicz; Eliza Garbacz; Agnieszka Pocheć; Bartosz Lautenbach; Dariusz Nędza; Klaudia Wojciech; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cardiovascular diseases (CVDs) remain the leading global cause of mortality, with physical inactivity contributing substantially to their development. Regular physical activity improves endothelial function, cardiometabolic health, inflammatory balance and cardiorespiratory fitness, which are key factors in reducing CVD risk.Aims: The aim of this narrative review was to synthesise current epidemiological, interventional and mechanistic evidence on the role of physical activity in reducing cardiovascular disease risk in adults.Methods: A structured narrative review was conducted using literature from PubMed, Scopus, Web of Science and Google Scholar (January–March 2025). Eligible studies examined adults (≥18 years), assessed physical activity or structured exercise as the main exposure and reported outcomes including blood pressure, lipid profile, glucose metabolism, inflammatory markers, vascular function, cardiorespiratory fitness or CVD incidence. Randomised controlled trials, cohort studies, cross-sectional studies and systematic or narrative reviews were included.Results: Evidence from randomised trials shows that aerobic, resistance and combined exercise programs reduce blood pressure, improve lipid levels, enhance insulin sensitivity and increase cardiorespiratory fitness. Cohort studies demonstrate that higher habitual activity is associated with lower risks of coronary heart disease, stroke and cardiovascular mortality. Cross-sectional findings support favourable biomarker profiles, while systematic reviews highlight consistent mechanisms and dose–response patterns. Sedentary behaviour remains an independent predictor of cardiovascular risk.Conclusion: Physical activity is an effective, accessible strategy for reducing cardiovascular disease risk. Promoting regular movement and limiting sedentary time should remain central elements of cardiovascular prevention.